A morphometric sexing approach for the Ring-necked Parakeet Psittacula krameri in Italy. Issue 2 (3rd July 2018) - Mentil, Lorenzo; Monti, Paolo; Fraticelli, Fulvio; Carpaneto, Giuseppe Maria
ABSTRACT: Only one fact is certain when sexing the Ring-necked Parakeet visually: adult males have a rose-coloured ring and a black bib that is fully developed by their third year. Sexually immature males (those <3 years old) and females are considered impossible to separate without using biometric measures, some additional to those in previous literature. While the biometrics of males and females overlap broadly in value, males tend to be slightly larger than females in all measurements. We tested the possibility of sexing individuals of this species using a series of biometric measurements. A total of 97 parakeets were captured and measured in 2016–17. Measurements of wing length, tail length, bill length, height and thickness, tarsus length, mass, third-primary length and number of yellow underwing coverts were recorded for these individuals. In addition, photographs of the head and wing were taken. Feather samples were taken from all individuals for DNA extraction and 45 of these birds (26 females and 19 males) have been sexed. The measurements from these known-sex individuals were pooled with the measurements for adult males and a logistic regression of the known sexes was performed to verify whether the mean value of the biometric variables was statistically different between females and males. We found that it is possible to separate the sexes using morphological measures of wing, tail, bill length and thickness, tarsus and the number of yellow underwing coverts.